Backside Contacting for Uniform Luminance in Large-Area OLED. (15th February 2017) - Pfeiffer, P.; Zhang, X. D.; Stümmler, D.; Sanders, S.; Weingarten, M.; Heuken, M.; Vescan, A.; Kalisch, H.
ABSTRACT: We have investigated organic light emitting diode (OLED) backside contacting for the enhancement of luminance uniformity as a superior alternative to gridlines. In this approach, the low-conductivity OLED anode is supported by a high-conductivity auxiliary electrode and vertically contacted through via holes. Electrical simulations of large-area OLEDs have predicted that this method allows comparable luminance uniformity while sacrificing significantly less active area compared to the common gridline approach. The method for fabricating backside contacts is comprised of five steps: (1) Thin-film encapsulation of the OLED, (2) Patterning of the OLED surface with lithography (resist mask defining via hole positions), (3) Via hole formation to the bottom anode by a plasma etching process, (4) Organic residues removal and sidewall insulation. (5) Contacting of the anode with a high-conductivity auxiliary electrode. Backside-contacted OLEDs processed by organic vapor phase deposition show high luminance uniformity. Scanning electron microscopy pictures and electrical breakthrough measurements confirm efficient sidewall insulation.